2021
DOI: 10.48550/arxiv.2108.03984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engineering Proximity Exchange by Twisting: Reversal of Ferromagnetic and Emergence of Antiferromagnetic Dirac Bands in Graphene/Cr$_2$Ge$_2$Te$_6$

Klaus Zollner,
Jaroslav Fabian

Abstract: We investigate the twist-angle and gate dependence of the proximity exchange coupling in twisted graphene on monolayer Cr2Ge2Te6 from first principles. The proximitized Dirac band dispersions of graphene are fitted to a model Hamiltonian, yielding effective sublattice-resolved proximityinduced exchange parameters (λ A ex and λ B ex ) for a series of twist angles between 0 • and 30 • . For aligned layers (0 • twist angle), the exchange coupling of graphene is the same on both sublattices, λ A ex ≈ λ B ex ≈ 4 me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Note that, similar to the TMDCs, CGT also shows a strain-tunable band gap [121][122][123]. Again, the twist angle is crucial for proximity exchange in graphene/CGT heterostructures [40]. In our geometries, the relative twist angle between top (bottom) CGT and the top (bottom) graphene layer is 30 • .…”
Section: A Geometry Setupmentioning
confidence: 72%
See 2 more Smart Citations
“…Note that, similar to the TMDCs, CGT also shows a strain-tunable band gap [121][122][123]. Again, the twist angle is crucial for proximity exchange in graphene/CGT heterostructures [40]. In our geometries, the relative twist angle between top (bottom) CGT and the top (bottom) graphene layer is 30 • .…”
Section: A Geometry Setupmentioning
confidence: 72%
“…In Ref. [40], it has been explicitly shown by DFT calculations, that mainly twisting influences proximity exchange, while straining determines the position of the graphene Dirac states within the CGT band gap. This band offset is again tunable by gating, thereby influencing proximity exchange.…”
Section: A Geometry Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Twistronics is now demonstrating its potential for proximity effects. It is revealed that twisting has profound influences on both the magnitude and the type of proximity induced SOC in graphene/TMDC heterostructure [61] as well as proximity exchange coupling in graphene/Cr 2 Ge 2 Te 6 heterostructure and emergence of antiferromagnetic Dirac bands in graphene [62]. Remarkably, wide tunability of the proximity exchange coupling has been reported in TMDC/CrI 3 heterostructures through controlling the interlayer twist between layers and electrostatic gating [63].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of superconductivity in magic-angle twisted bilayer graphene [40][41][42][43] gave the impetus for twistronics [44][45][46][47], recognizing the twist angle as a critical new control parameter for tailoring electronic properties of van der Waals heterostructures [48][49][50][51][52]. It is then natural to ask how does the twist angle influence proximity SOC in graphene.…”
Section: Introductionmentioning
confidence: 99%